The Uncertainty about the Total Economic Impact of Climate Change - TOL, RICHARD S. J. (ESRI)
This paper uses a vote-counting procedure to estimate the probability density function of the total economic impact as a parabolic function of global warming. There is a wide range of uncertainty about the impact of climate change up to 3?C, and the information becomes progressively more diffuse beyond that. Warming greater than 3?C most likely has net negative impacts, and warming greater than 7?C may lead to a total welfare loss. The expected value of the social cost of carbon is about $29/tC in 2015 and rises at roughly 2% per year.
PUBLISHED
Keywords: impacts; cost; Social cost of carbon; Climate change; uncertainty